Liga Arab dan Demokratisasi di Dunia Arab - Sugito, Sugito (Jurnal Hubungan Internasional, 2012)
Arab world never deserted from International discussions. It related to long drawn conflict in that region, such as conflict of Palestine and Israel, Iraq condition after US attack, also terrorism issues which alleged to this region. The Arab world became identical with a region which full of conflict and have no political certainty. On this condition, Arab League as institutional cooperation of countries in this region forced to have articulative roles.